2011
DOI: 10.1080/09585192.2011.559097
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the paradox of employers' views about older workers

Abstract: In advanced and developing economies, ageing populations and low birth rates are emphasising the need for retaining and sustaining competent older workers. This paper examines policy and practice implications from the contradictory accounts directed towards those workers aged over 44 years whom are usually classified as "older workers". It focuses on a key and paradoxical impediment in the retention of these workers in labour forces. That is, despite their increasing dependence on older workers, employers ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 12 publications
6
66
0
6
Order By: Relevance
“…In the literature it is stated that aging workers have less capability to learn in comparison to their younger colleagues, especially because of the general cognitive and sensorial decline associated with age. Aging employees are slower in performing learning tasks and experience more difficulties to reach the same performance level as younger workers at the end of a training program (Billett, Dymock, Johnson, & Martin, 2011;. This belief is consistent with the idea, highlighted in developmental psychology, of a deceleration of cognitive functioning with increased age.…”
Section: Capability To Learnsupporting
confidence: 82%
“…In the literature it is stated that aging workers have less capability to learn in comparison to their younger colleagues, especially because of the general cognitive and sensorial decline associated with age. Aging employees are slower in performing learning tasks and experience more difficulties to reach the same performance level as younger workers at the end of a training program (Billett, Dymock, Johnson, & Martin, 2011;. This belief is consistent with the idea, highlighted in developmental psychology, of a deceleration of cognitive functioning with increased age.…”
Section: Capability To Learnsupporting
confidence: 82%
“…employability, work motivation, and health) has become apparent (De Vos & van der Heijden, 2015). Many organizations develop HRM policies and actions, and implement practices aimed at increasing workers' sustainable employability at work (Billett, Dymock, Johnson, & Martin, 2011;Semeijn, van Dam, van Vuuren, & van der Heijden, 2015;van Harten, Knies, & Leisink, 2016;Veth, Emans, van der Heijden, Korzilius, & De Lange, 2015). Until now, there is only limited research examining what HR practices employers implement and how effective these practices are.…”
Section: Introductionmentioning
confidence: 99%
“…The presented findings add to the scholarly understanding of how organizations use frames to give meaning to workforce aging, which, in turn, may help to facilitate and manage demographic changes within organizations. The results suggest that organizations are paradoxically caught between resistance to fundamentally change existing organizational practices and labor agreements and the pressures from government and society to deal with the issue of sustainable employability (see also Billett et al, 2011). We have shown that organizations frame the issue in a strategic manner, using prognostic and culturallyresonant frames in (especially external) communication while silencing frames that problematize the issue or that break with current conventions.…”
Section: Discussionmentioning
confidence: 95%